Exploring the Potential of Robocasting for High-Density Electrolytes in Solid Oxide Fuel Cells - Lidia Licu; Alexandru-Cristian Matei; Ștefania Caramarin; Florentina-Gabriela Ioniță; Dumitru-Valentin Drăguț; Alexandru Okos; Dan-Năstase Ciobota (Inorganics)
This study investigates the application of robocasting technology for fabricating high-density yttria-stabilized zirconia (8YSZ) electrolytes used in solid oxide fuel cells (SOFCs). The primary goal is to overcome the limitations of traditional manufacturing techniques, such as low density and poor microstructural control. Using a combination of hydrothermal synthesis, rheological testing, and robocasting, we achieved dense 8YSZ structures (over 95% density) with minimal porosity. The fabricated electrolytes underwent sintering and debinding processes, with thermal treatment profiles optimized for structural integrity. A microstructural analysis through SEM and XRD confirmed the formation of stable crystalline phase. This research opens new avenues for the use of additive manufacturing in electrochemical applications, particularly for producing complex ceramic components with superior characteristics.